Lanthanide–uranyl phosphonates constructed from diethyl ((phenylsulfonyl)methyl)phosphonate. Issue 3 (22nd December 2021) - Hou, Xiaomin; Tang, Si-Fu
Abstract : Lanthanide–uranyl sulfonylphosphonates with intriguing crystal structures and photophysical properties can be assembled from a heterofunctional diethyl phosphonate precursor ligand. Abstract : Lanthanide–uranyl phosphonates possess intriguing crystal structures and huge application prospects, but the construction of these materials remains challenging. In this work, we demonstrate that new uranyl and lanthanide–uranyl sulfonylphosphonates with elegant crystal structures and photophysical properties can be assembled hydrothermally by employing the heterofunctional diethyl phosphonate (diethyl ((phenylsulfonyl)methyl)phosphonate, Et2 L) as a precursor ligand, which provides an effective strategy for the construction of lanthanide–uranyl phosphonates.